HyProCure for progressive collapsing foot deformity: is subtalar arthroereisis a good procedure? - Shaoling Fu; Cheng Wang; Shutao Zhang; Chenglin Wu; Jiazheng Wang; Zhongmin Shi (Journal of Orthopaedic Surgery and Research)
Abstract Purpose To investigate the treatment outcomes of subtalar arthroereisis (SA) in progressive collapsing foot deformity (PCFD) patients, to assess the clinical efficacy in PCFD patients after HyProCure removal, and to evaluate safety and effectiveness of SA. Methods In this retrospective study, 202 cases (213 feet) of PCFD patients treated with SA from June 2015 to December 2022 were selected. General data and surgical information were recorded, and clinical efficacy was evaluated through imaging and clinical indicators. Furthermore, for 36 patients (36 feet) who underwent secondary surgery to remove HyProCure, imaging and clinical evaluation indicators at 1-year post-removal were recorded. Complications were also documented. Results The main complications were sinus tarsi pain (91.37%), with partial relief or disappearance of symptoms in some patients after conservative treatment. The imaging indicators improved significantly after SA (P < 0.01), and AOFAS score and VAS were significantly improved (P < 0.01), with a 100% excellent rate in patients one year after SA. For patients who removed HyProCure, the imaging indicators exhibited a significant improvement at preoperation and post-SA (P < 0.01), and no statistical difference was observed between post-SA and post-removal (P > 0.05). Regarding clinical indicators, AOFAS score at post-SA was difference compared with preoperation and post-removal separately (P < 0.01). However, the difference in VAS between preoperation and post-SA was not statistically significant (P > 0.05). Notably, there was a significant improvement at post-removal compared with post-SA (P < 0.01). Conclusion PCFD patients showed significant improvement in imaging and clinical evaluations after SA, with no significant flatfoot recurrence in patients who had HyProCure removed. Therefore, the application of HyProCure in SA can be considered a safe and effective surgical treatment for PCFD patients.